PERSONAL AND SPATIAL DEIXIS ON THE SONG LYRICS OF “SUNDAY BEST” BY SURFACES - Aurelia, Ananda Winda; Suprijadi, Dasep; Husnussalam, Hendra (IKIP Siliwangi, 2022)
This study aimed to find out the use of personal and spatial deixis on the song lyrics of “Sunday Best” by Surfaces, and also to describe the meaning of this song. This study used the qualitative method. The writer used document analysis as the instrument of this study, while the data collection techniques that have been conducted listened to that music, collecting that song lyrics script on the internet, then analyzing the use of personal and spatial deixis on that song. The results of this study showed that personal deixis became the dominant type of spatial deixis. There are 30 data of personal deixis consisting of first, second, and third person deixis. Meanwhile, the writer only found 6 data of spatial deixis. The meaning has been found after the writer listened to this song and analyzed it using personal and spatial deixis. The writer notes that by using personal and spatial deixis it will make easily to catch the reference meaning that include who, where and why the utterance is uttered. Keywords: Pragmatics, Deixis, Song Lyrics